2013
DOI: 10.1109/tvcg.2013.197
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Awareness through Collaborative Brushing and Linking of Tabular Data

Abstract: Maintaining an awareness of collaborators' actions is critical during collaborative work, including during collaborative visualization activities. Particularly when collaborators are located at a distance, it is important to know what everyone is working on in order to avoid duplication of effort, share relevant results in a timely manner and build upon each other's results. Can a person's brushing actions provide an indication of their queries and interests in a data set? Can these actions be revealed to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Furthermore, users can easily lose awareness for what others are doing while working on a different area of the large display [36,43,60,81]. Gutwin & Greenberg [36] state that to maintain workspace awareness, users need to monitor each other's behavior, for instance by showing past interactions of others [37], incorporating visual connections between information [42], using ambient light [65], or embedding animation and off-screen visualization techniques [35,66]. Personal Territories: Studies have shown that users value a personal territory to interact with while still maintaining shared spaces [77,81].…”
Section: C3 Support For Multiple Usersmentioning
confidence: 99%
“…Furthermore, users can easily lose awareness for what others are doing while working on a different area of the large display [36,43,60,81]. Gutwin & Greenberg [36] state that to maintain workspace awareness, users need to monitor each other's behavior, for instance by showing past interactions of others [37], incorporating visual connections between information [42], using ambient light [65], or embedding animation and off-screen visualization techniques [35,66]. Personal Territories: Studies have shown that users value a personal territory to interact with while still maintaining shared spaces [77,81].…”
Section: C3 Support For Multiple Usersmentioning
confidence: 99%
“…Yet, a healthy level of interest in the topic persists in related disciplines such as information visualization and visual analytics (e.g. Chen, Alsakran, Barlowe, Yang, & Zhao, 2011;Donalek et al, 2014;Hajizadeh, Tory, & Leung, 2013;Isenberg et al, 2011;Mahyar, Sarvghad, & Tory, 2010;Wu, Convertino, Ganoe, Carroll, & Zhang, 2013). This is a curious turn of events given that the growth of Web 2.0 technologies such as Twitter or Facebook and VGI have arguably greatly increased the level of collaboration worldwide on geospatial problems.…”
Section: With Whom Is An Activity Undertaken?mentioning
confidence: 99%
“…In HCI, Isenberg and Fisher propose visual cues for group awareness in document queries and searching activities [24]. In InfoVis, Hajizadeh et al demonstrate the effects of awareness in tabular data [16], and Mahyar and Tory show the efficiency benefits of presenting awareness in linked common work (LCW) [29]. Results from these studies indicate that a group can benefit from sharing knowledge and understanding of activities that others are performing [19,24].…”
Section: Supporting Group Tasks With Visualizationmentioning
confidence: 99%
“…Results from these studies indicate that a group can benefit from sharing knowledge and understanding of activities that others are performing [19,24]. In certain instances, group awareness can also help avoid redundant work [16]. Evidence from these prior studies suggests that group awareness could improve group decision-making tasks by enabling the group members to share their intention in visual format and thereby reduce the communication costs required for establishing common ground.…”
Section: Supporting Group Tasks With Visualizationmentioning
confidence: 99%